Outlander : Season two, disc 3 - Balfe, Caitriona; Heughan, Sam, 1980-; Lacroix, Duncan; Sony Pictures Home Entertainment (Firm) (Culver City, California Sony Pictures Home Entertainment, 2016)
Follows the story of Claire Randall, a married combat nurse from 1945 who is mysteriously swept back in time to 1743, where she is immediately thrown into an unknown world where her life is threatened. When she is forced to marry Jamie Fraser, a chivalrous and romantic young Scottish warrior, a passionate relationship is ignited that tears Claire's heart between two vastly different men in two irreconcilable lives. In Season 2, Claire and Jamie arrive in France, hell-bent on infiltrating the Jacobite rebellion led by Prince Charles Stuart and stopping the battle of Culloden. With the help of Jamie's cousin, they are thrown into the lavish world of French society, where intrigue and parties are abundant but political gain proves far less fruitful. Altering the course of history presents challenges that begin to weigh on the very fabric of their relationship--but, armed with the knowledge of what lies ahead, Claire and Jamie must race to prevent a doomed Highland uprising and the extinction of Scottish life as they know it.
Faith -- The fox's lair -- Je Suis Prest.
Title from container.
Anamorphic widescreen (1.78:1).
Special features: deleted and extended scenes with introductions by Ronald D. Moore.
Caitriona Balfe, Sam Heughan, Duncan Lacroix.
CHV rating: 14A; sexual content, violence.
DVD.
Keywords: Nurses -- Great Britain -- Drama; Time travel -- Drama; Outlaws -- Scotland -- Drama; Man-woman relationships -- Drama; Scotland -- Drama; Great Britain; Drama; Fiction television programs; Historical television programs; Fantasy television programs; Action and adventure television programs; Television adaptations; Video recordings for the hearing impaired; Television series; Drama